Meta-Analysis: The Effect of Social Support on Medication Treatment Adherence in Tuberculosis Patients - Lily Nabillah; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Tuberculosis is a disease that can be cured by various methods of treatment. However, tuberculosis treatment is often not carried out properly and completely. The importance of medication adherence as a top priority in the effectiveness of treatment of tuberculosis patients through social support. The purpose of this study was to analyze the effect of social support on medication adherence in tuberculosis patients.Subjects and Method: This meta-analysis study used the PRISMA flowchart guideline with PICO, Population= Tuberculosis patients. Intervention= social support. Comparison= without social support. Outcome= medication adherence. The search process was carried out between 2017 and 2022 using Google Scholar, PubMed, Sci-Hub, and Science Direct databases. The keywords used were